1987
DOI: 10.1128/aac.31.5.723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of broad-spectrum parenteral antibiotics on "colonization resistance" of intestinal microflora of humans

Abstract: Studies with animals have shown that the normal intestinal microflora protects against colonization by new strains ("colonization resistance") and that this protective effect may be related to the anaerobic component of the microflora. However, colonization resistance has not been shown in humans. We administered cefoxitin, piperacillin, cefoperazone, and aztreonam intravenously to healthy subjects for 9 days and monitored the acquisition of new isolates in the fecal flora. Seven of sixteen antibiotic-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…Several studies have shown that oral or parenteral treatment with aztreonam in humans causes a pronounced decrease in the number of aerobic gram-negative rods without altering the composition of the anaerobic fecal flora (1,4,5,7,9,11,13). These results are explained by the intrinsic resistance of anaerobic bacteria to aztreonam.…”
supporting
confidence: 58%
“…Several studies have shown that oral or parenteral treatment with aztreonam in humans causes a pronounced decrease in the number of aerobic gram-negative rods without altering the composition of the anaerobic fecal flora (1,4,5,7,9,11,13). These results are explained by the intrinsic resistance of anaerobic bacteria to aztreonam.…”
supporting
confidence: 58%
“…In humans, a dramatic cure was reported in patients suffering from pseudomembranous colitis when fresh fecal suspensions were administered by an intrajejunal tube (9) or by enemas (9,41,46 (18). However, complete suppression of Shigella strains by E. coli was observed when the two organisms were introduced as the only flora in antibiotic-treated animals (20 (5). However, the concentration of cefoperazone in feces was more than 100-fold greater than the MICs for the challenge strains.…”
Section: Protective Function Of the Normal Floramentioning
confidence: 99%
“…When plasmid transfer occurs in the digestive tract, the resulting transconjugants are generally unable to become established in that indigenous bacterial community (Duval-Iflah et al, 1994). By contrast, the spreading of plasmids which encode resistance to clinically important antibiotics in pathogenic bacteria has been observed often during antimicrobial therapy, which is believed to modify the normal microbiota and to lower host resistance against colonization by pathogenic plasmid-bearing bacteria (Barza et al, 1987). In addition, it should be pointed out that there were R plasmids encoding, simultaneously, resistance, virulence and other features (Sant'Ana et al, 1995).…”
mentioning
confidence: 99%